Drought responsiveness in six wheat genotypes: identification of stress resistance indicators - Guizani, Asma; Askri, Hend; Amenta, Maria Laura; Defez, Roberto; Babay, Elyes; Bianco, Carmen; Rapaná, Nicoletta; Finetti-Sialer, Mariella; Gharbi, Fatma (Frontiers in Plant Science, 2023)
Introduction Wheat (Triticum aestivum L.) is among the world’s most important staple food crops. In the current climate change scenario, a better understanding of wheat response mechanisms to water stress could help to enhance its productivity in arid ecosystems. Methods In this study, water relations, gas exchange, membrane integrity, agronomic traits and molecular analysis were evaluated in six wheat genotypes (D117, Syndiouk, Tunisian durum7 (Td7), Utique, Mahmoudi AG3 and BT) subjected to drought-stress. Results and discussion For all the studied genotypes, drought stress altered leaf area, chlorophyll content, stomatal density, photosynthetic rate and water-use efficiency, while the relative water content at turgor loss point (RWC0) remained stable. Changes in osmotic potential at turgor loss point (Ψπ0), bulk modulus of elasticity (Ɛmax) and stomatal regulation, differed greatly among the studied genotypes. For the drought-sensitive genotypes AG3 and BT, no significant changes were observed in Ψπ0, whereas the stomatal conductance (gs) and transpiration rate (E) decreased under stress conditions. These two varieties avoided turgor loss during drought treatment through an accurate stomatal control, resulting in a significant reduction in yield components. On the contrary, for Syndiouk, D117, Td7 and Utique genotypes, a solute accumulation and an increase in cell wall rigidity were the main mechanisms developed during drought stress. These mechanisms were efficient in enhancing soil water uptake, limiting leaf water loss and protecting cells membranes against leakage induced by oxidative damages. Furthermore, leaf soluble sugars accumulation was the major component of osmotic adjustment in drought-stressed wheat plants. The transcriptional analysis of genes involved in the final step of the ABA biosynthesis (AAO) and in the synthesis of an aquaporin (PIP2:1) revealed distinct responses to drought stress among the selected genotypes. In the resistant genotypes, PIP2:1 was significantly upregulated whereas in the sensitive ones, its expression showed only a slight induction. Conversely, the sensitive genotypes exhibited higher levels of AAO gene expression compared to the resistant genotypes. Our results suggest that drought tolerance in wheat is regulated by the interaction between the dynamics of leaf water status and stomatal behavior. Based on our findings, Syndiouk, D117, Utique and Td7, could be used in breeding programs for developing high-yielding and drought-tolerant wheat varieties.